eCM 2017
DOI: 10.22203/ecm.v033a21
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin alleviates lumbar radiculopathy by reducing neuroinflammation, oxidative stress and nociceptive factors

Abstract: Current non-surgical treatments for lumbar radiculopathy [e.g. epidural steroids and Tumour necrosis factor-α (TNF-α) antagonists] are neither effective nor safe. As a non-toxic natural product, curcumin possesses an exceptional anti-inflammatory profile. We hypothesised that curcumin alleviates lumbar radiculopathy by attenuating neuroinflammation, oxidative stress and nociceptive factors. In a dorsal root ganglion (DRG) culture, curcumin effectively inhibited TNF-α-induced neuroinflammation, in a dose-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 55 publications
4
73
0
2
Order By: Relevance
“…In an LPS-induced PD model, curcumin inhibits astrocyte activation and NADPH oxidase complex activation by downregulating NF- κ B activity, intrinsic apoptotic pathway (Bax, Bcl-2, caspase 3, and caspase 9), proinflammatory cytokines (TNF- α , IL-1 β , and IL-1 α ), and inducible NOS [ 79 ]. In primary neuron culture, curcumin effectively inhibits TNF- α -induced neuroinflammation (IL-6 and Cox-2), protects neurons from excessive ROS production and cellular apoptosis, and promotes expression of antioxidative enzymes HO-1, catalase, and SOD-2 [ 80 ]. Recently, conjugated curcumins such as nanocurcumin or curcumin-like analogs are developed to increase their bioavailability and potential neuroprotective efficacy in PD.…”
Section: Brain Innate Immunity Regulation By Phytochemicals and Itmentioning
confidence: 99%
“…In an LPS-induced PD model, curcumin inhibits astrocyte activation and NADPH oxidase complex activation by downregulating NF- κ B activity, intrinsic apoptotic pathway (Bax, Bcl-2, caspase 3, and caspase 9), proinflammatory cytokines (TNF- α , IL-1 β , and IL-1 α ), and inducible NOS [ 79 ]. In primary neuron culture, curcumin effectively inhibits TNF- α -induced neuroinflammation (IL-6 and Cox-2), protects neurons from excessive ROS production and cellular apoptosis, and promotes expression of antioxidative enzymes HO-1, catalase, and SOD-2 [ 80 ]. Recently, conjugated curcumins such as nanocurcumin or curcumin-like analogs are developed to increase their bioavailability and potential neuroprotective efficacy in PD.…”
Section: Brain Innate Immunity Regulation By Phytochemicals and Itmentioning
confidence: 99%
“…It is known that macrophages show these effects by increasing the function of factors such as TGF-β, TGF-α, basic FGF, PDGF and vascular endothelial growth factor that increase proliferation and cell synthesis. Several studies suggest that curcumin decreases the amount of these factors (23). On the other hand, IL-6 and TGF-β1 has been shown to be effective on EF (3).…”
Section: █ Conclusionmentioning
confidence: 99%
“…Prior studies have also suggested that this mediator induces the amount of IL-6, prostaglandin E2 (PGE2), cyclooxygenase (COX-2) that have an important role in inflammation. Curcumin suppresses TNF-α-induced neuroinflammation IL-6, PGE2, COX-2 at a significant level (23). Moreover; curcumin has been shown to decrease post traumatic inflammation due to its anti-inflammatory properties in experimental spinal cord trauma studies (2).…”
Section: █ Conclusionmentioning
confidence: 99%
“…Under a hypoxic state it can increase the permeability of BBB by upregulating the expression of heme oxygenase-1 (HO-1) in microvascular endothelial cells 164 . In addition, Xiao et al 165 showed that curcumin can protect neurons from TNF- α -triggered excessive ROS production and cellular apoptosis. Correspondingly, it promoted mRNA expression of anti-oxidative enzymes like HO-1, catalase and superoxide dismutase-2.…”
Section: Natural Products Regulating the Bbb Microenvironmentmentioning
confidence: 99%